Referral Prioritization in Home Care Occupational Therapy: A Matter of Perspective. (June 2020) - Raymond, Marie-Hélène; Feldman, Debbie Ehrmann; Demers, Louise
Background: Prioritizing referrals for home care occupational therapy is somewhat subjective, and public and patient perspectives on waiting list priorities are unknown. Purpose: To explore the views of home care occupational therapists (OTs), older persons (OPs) and adults with disabilities on waiting list priorities, as well as issues and challenges underlying these priorities. Method: We conducted in-depth interviews with 11 OTs, 10 OPs and 9 adults with disabilities. Participants were asked to prioritize referral scenarios while explaining their choices. Directed and conventional content analysis allowed the identification of themes for each group of participants. Findings: OTs experienced conflicts of values but mainly prioritized referrals based on client safety. OPs sought to maximize client's independence, and persons with disabilities aimed to improve clients' social participation. Implications: OTs should seek the perspectives of their target clientele on referral prioritization criteria and strive to adjust prioritization practices accordingly.